O13.2 Molecular epidemiology in relation to azithromycin resistance in neisseria gonorrhoeae isolates from amsterdam, the netherlands, between 2008 and 2015 – a case-control study. (8th July 2017) - Dam, Alje PVan; Wind, Caroline; Loeff, Maarten Schim Van Der; Vries, Henry De; Dierdorp, Mirjam; Bruisten, Sylvia
Abstract : Neisseria gonorrhoeae resistance to ceftriaxone and azithromycin increases, which threatens the recommended dual therapy based on these antimicrobials. We used molecular epidemiology to identify N. gonorrhoeae clusters, and associations with azithromycin resistance in Amsterdam, the Netherlands. N. gonorrhoeae isolates were selected from patients visiting the Amsterdam Sexually Transmitted Infections Clinic, from January 2008 through September 2015. We included all azithromycin resistant isolates (minimum inhibitory concentration [MIC] ≥2.0 mg/L), and frequency matched susceptible controls (MIC ≤0.25 mg/L). All isolates were tested using 23S rRNA sequencing, N. gonorrhoeae multiantigen sequence typing (NG-MAST), and multilocus variable-number of tandem repeat analysis (NG-MLVA). A hierarchical cluster analysis of NG-MLVA related to resistance and epidemiological characteristics was performed. We analysed 143 isolates (69 resistant and 74 susceptible); 81% was from men who have sex with men (MSM). Azithromycin resistant isolates had significantly more often C2611T mutations of 23S rRNA (n=62, 89.9%, p<0.001), an NG-MAST genogroup G2992 (p<0.001), G5108 (p<0.001), or G359 (p=0.02), and were more often part of NG-MLVA clusters (p<0.001). Two resistant isolates (2.9%) had A2059G mutations, and five (7.3%) were wild-type 23SrRNA. Four of the five NG-MLVA clusters contained resistant and susceptible isolates, and isolates from HIV-positive and HIV-negative patients. Two of the clusters consisted mainly of resistant isolates and were strains from MSM, heterosexual men and women. Co-occurrence of resistant and susceptible strains in NG-MLVA clusters and frequent occurrence of resistant strains outside of clusters suggests that azithromycin resistance develops independently from the 'background genome'.